Effects of tumor treating fields (TTFields) on human mesenchymal stromal cells - Strack, Maren; Kückelhaus, Jan; Diebold, Martin; Wuchter, Patrick; Huber, Peter E.; Schnell, Oliver; Sankowski, Roman; Prinz, Marco; Grosu, Anca-Ligia; Heiland, Dieter Henrik; Nicolay, Nils; Rühle, Alexander (Journal of neuro-oncology, 2024)
Mesenchymal stromal cells (MSCs) within the glioblastoma microenvironment have been shown to promote tumor progression. Tumor Treating Fields (TTFields) are alternating electric fields with low intensity and intermediate frequency that exhibit anti-tumorigenic effects. While the effects of TTFields on glioblastoma cells have been studied previously, nothing is known about the influence of TTFields on MSCs.